Minecraft Game as a New Opportunity for Teaching Renewable Energy Topics - Kersánszki, Tamás; Holik, Ildikó; Márton, Zoltán (International Journal of Engineering Pedagogy (iJEP), 2023)
In today’s Public Education Sector, the need for creative education is becoming more and more prominent. An excellent method for achieving this is gamification, which provides an opportunity to activate and motivate students by playfully processing the desired knowledge material. Minecraft is a multi-platform video game that can be successfully used in gamified education. This game platform is used at one of the summer camps we announced for elementary and high school students (10–16 years old). The participants mastered the topics of renewable energy sources with the help of the Minecraft game. This study describes the methods used in the camp and presents the research results on the effectiveness of the camp. The students’ current level of knowledge was examined with a questionnaire about renewable energy sources, and the collaborative skills questionnaire was used to assess the collaboration characteristics, and the school creative climate questionnaire was used to explore specific features of the camp. The practical results of the camp and the research results proved that gamification, the use of Minecraft, was excellent for arousing students’ interest, increasing their motivation, and helping them master the knowledge materials, effective task solving, and cooperation (i.e., the camp was equally effective from the point of view of knowledge acquisition and collaboration).